Genetic Study In a Pakistani Family Reveals Autosomal Recessive Type of Artemis Deficiency - Ayub, Saddaf; Zainub, Abeerah; Shafi, Nida; Khan, Zara Khalid; Siddique, Lubna; Raza, Syed Irfan (Journal of Rawalpindi Medical College, 2025)
Objective: To perform clinical and genetic investigations in two patients suffering from Artemis deficiency with total deficiency of T-B- lymphocytes. Methods: We enrolled a Pakistani family with one male patient suffering from Severe Combined Immune Deficiency (SCID). Immunological investigations including lymphocyte subset analysis, and serum immunoglobulin levels were performed. Genetic analysis was performed on patients and available parents. Polymerase Chain Reaction (PCR) based amplification and electrophoresis in patients, parents and control was performed. Results: A detailed clinical investigation revealed mild fever, lower respiratory tract infections, watery diarrhoea, and oral moniliasis from the age of one month. Lymphocyte subset analysis showed T-/B- and NK+ type SCID. Genetic analysis revealed two exon deletions in the Artemis encoding gene (DCLRE1C, OMIM 602450). Conclusion: This study reveals a novel mega deletion mutation in the gene DCLRE1C, (two exon deletions) confirmed through PCR-based electrophoresis. The mutation leads to Artemis deficiency T-/B-/NK+ type of SCID. Keywords: CNV repeats, SCID, Artemis deficiency, Lymphocyte subset analysis, Immunoglobulins.